Combination Ciprofloxacin and Metronidazole for Active Crohn’s Disease - Susan L Greenbloom; A Hillary Steinhart; Gordon R Greenberg (Canadian Journal of Gastroenterology)
Recent experimental evidence underscores the contribution of intestinal bacteria to the inflammatory process of Crohn's disease. This open study examined the efficacy and safety of combination ciprofloxacin and metronidazole for patients with active Crohn's disease of the ileum and/or colon. Seventy-two patients with active Crohn's disease of the ileum (n=27), ileocolon (n=22) or colon (n=23) were treated with ciprofloxacin 500 mg bid and metronidazole 250 mg tid for a mean of 10 weeks. Clinical remission was defined as a Harvey-Bradshaw index of three points or less; an index reduction of at least three points indicated a clinical response. Clinical remission was observed in 49 patients (68%), and 55 patients (76%) showed a clinical response. A clinical response was noted in 29 of 43 patients (67%) who were not taking concurrent prednisone treatment and in 26 of 29 patients (90%) receiving prednisone (mean dose of 15 mg/day). A clinical response also occurred in a greater proportion of patients with colonic disease, with or without ileal involvement (84%), compared with patients with ileal disease alone (64%), and in patients without resection (86%) compared with those with previous resection (61%). Five patients discontinued antibiotics because of adverse events. After a mean follow-up of nine months, clinical remission was maintained in 26 patients off treatment and in 12 patients who continued antibiotic therapy. Ciprofloxacin in combination with metronidazole is well tolerated and appears to play a beneficial role in achieving clinical remission for patients with active Crohn's disease, particularly when there is involvement of the colon.